Working Memory Load Selectively Influences Response Inhibition in a Stop Signal Task. Issue 3 (June 2021) - Boucher, Leanne; Viparina, Brandi; Collins, W. Matthew
Inhibitory control is a key executive function and has been studied extensively using the stop signal task. By applying a simple race model that posits an independent race between a GO process responsible for initiation of responses and a STOP process responsible for inhibition of responses, one can estimate how long it takes an individual to inhibit an ongoing response, the stop signal reaction time. Here, we examined how stop signal reaction time can be affected by working memory. Participants engaged in a dual task; they completed a stop signal task under low and high working memory load conditions. Working memory capacity was also measured. We found that the STOP process was lengthened in the high, compared to the low, working memory load condition, as evidenced by differences in stop signal reaction time. The GO process was unaffected and working memory capacity could not account for differences across the load conditions. These results indicate that inhibitory control can be influenced by placing demands on working memory.